MONITORING KONDISI PAHAT DENGAN SINYAL GETARAN PADA PROSES BUBUT - Rusnaldy, Rusnaldy; Setiawan, Joga Dharma; Arivian, Anggi (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2011)
Turning process plays an important role in manufacturing industry. Almost all cilyndrical specimen worked with turning machine. But the unperfect process is often unrealized by the operator. Thus, we need a method to monitor a tool condition. The objective of this study is to introduce a method of tool condition monitoring during a turning process. In this study, vibration signal was used to monitor tool condition. Two kind of tool conditions were used, new tool and tool with built-up-edge (BUE). During a turning process the vibration of the tool was measured. Surface roughness of machined surface was measured after turning process. The results show that vibration signal can be implemented as a tool for monitoring a tool condition. Tools with BUE have high vibration amplitude, vibration amplitude increases with increase the BUE area. Cutting with these tools can cause plowing or rubbing, resulting in a poor surface due to high friction.